Social Prestige and Islamic Maslahah in Marriage Gift Traditions: A Socio-Legal Study of Coastal Muslim Communities - Muhammad Alif Syaihoni; Pujiono Hamid; Abdul Wahab (Al-Qalam Institue, 2026)
The tradition of wedding gift-giving remains a crucial component of marital practices in many Muslim societies, serving not only as a cultural ritual but also as a social institution that shapes relationships, status, and communal recognition. This study examines the socio-legal dimensions of the tradition of wedding gift-giving (seserahan) among coastal Muslim communities, with particular attention to the interplay between social prestige and Islamic maslahah (benefit). Using a qualitative socio-legal approach, data were collected through semi-structured interviews, participant observation, and document analysis involving religious leaders, community leaders, wedding officiants, family members, and local residents. The findings indicate that wedding gifts serve as a form of symbolic capital through which families gain social recognition, maintain family honor, and strengthen communal legitimacy. This tradition contributes to social cohesion by strengthening kinship ties, fostering solidarity, and supporting family integration. However, the study also found that contemporary socio-economic changes increasingly link wedding gifts to prestige competition, leading to increased social expectations and, in some cases, financial burdens on families. The tradition of wedding gift-giving aligns with Islamic principles when it promotes social welfare, protects family dignity, and strengthens social harmony. Conversely, when prestige-oriented motivations override welfare considerations, the tradition risks giving rise to forms of social and economic hardship that contradict the aims of Islamic law.